THE EFFECTIVENESS OF COLLABORATIVE LEARNING IN DEVELOPING COMMUNICATION SKILLS IN ESL - Zebo Xakimjon Kizi, Botirova; Zebona Xayrulla Kizi, Sayfiddinova (PT. Antis International Publisher, 2025)
Objective: This study explores the effectiveness of collaborative learning in enhancing communication skills among English as a Second Language (ESL) learners. The focus is on understanding how this instructional approach contributes to the development of linguistic and interpersonal abilities. Methods: The research involves a review of theoretical frameworks and empirical studies on collaborative learning. It emphasizes the implementation of small-group activities aimed at achieving shared goals, analyzing their impact on active communication, language proficiency, and social interactions in ESL contexts. Results: Findings indicate that collaborative learning significantly improves speaking and listening skills, boosts learners' confidence, and facilitates peer-to-peer learning. Additionally, it promotes a supportive environment that enhances both linguistic and social competencies. Novelty: By synthesizing theoretical insights and empirical evidence, this study highlights the underexplored potential of collaborative learning as a transformative tool in ESL education. It offers actionable recommendations for incorporating these strategies into instructional practices, making a meaningful contribution to the field.